Extrauterine Growth Restriction in Very Low Birth Weight Infants: Concordance Between Fenton 2013 and INTERGROWTH-21st Growth Charts - González-García, Lara; García-López, Enrique; Fernández-Colomer, Belén; Mantecón-Fernández, Laura; Lareu-Vidal, Sonia; Suárez-Rodríguez, Marta; Arias-Llorente, Rosa Patricia; Solís-Sánchez, Gonzalo (Frontiers in Pediatrics, 2021)
Postnatal growth restriction has high prevalence in very low birth weight (VLBW) preterm neonates and this could affect their long-term prognosis. Nowadays there is no consensus on how to monitor growth in these neonates. Objective: To compare prevalence of intra- and extrauterine growth restriction (IUGR and EUGR) in a sample of very low birth weight (VLBW) infants according to Fenton 2013 charts and INTERGROWTH-21st (IW-21) standards, and to analyze concordance between both in the different EUGR definitions criteria (cross-sectional, dynamic and true). Patients and methods: Observational retrospective study of 635VLBW preterm. Study was carried out in Central Universitary Hospital of Asturias. Body measurements (weight, length and head circumference) were collected at birth and at hospital discharge and expressed in z-scores for the two references (Fenton 2010 and IW-21). Kappa concordance was calculated. Results: Kappa concordance between Fenton and IW-21 was 0.887 for IUGR and 0.580 for static EUGR. Prevalence was higher according Fenton in IUGR (36.5% vs 35.1%),in static EUGR (73.8% vs 59.3%) and in dynamic EUGR(44.3% vs 29.3%). Despite observing low prevalence of EUGR when IW-21 was used to define EUGR, it was observed a statistical association between neonatal morbidity and diagnosis of EUGR. Conclusion: Fenton and IW-21concordancefor IUGR is good. IW-21 is more restrictive than Fenton in EUGR. Patients diagnosed by IW-21 as EUGR are more likely to have neonatal morbidity, especially if we use EUGR dynamic definition. In our study we cannot conclude that one graph is better than the other.